Po co Peiper? - Fazan, Jarosław (Przestrzenie Teorii, 2024)
The article confronts Tadeusz Peiper’s ideas contained in his programme manifestos, published mainly in the pages of “Zwrotnica” in the 1920s, with the evolution of modern civilisation. The fundamental problem is the failure of the optimistic vision of the materialist turn when confronted with economic, social and ecological crisis. The sketch draws attention to the ‘flight from freedom’ embodied in avant-garde manifestos and the divergence of Peiperian rationalism from the realities of the post-World War I world.